Evaluating the Effectiveness of Perineural Nerve Block with Ropivacaine and Dexamethasone in Patients with Neurogenic Thoracic Outlet Syndrome—A Prospective Pilot Trial - Lucia Winkler; Christian Smolle; Andreas Fellner; Lars-Peter Kamolz; Werner Girsch (Surgeries, 2025)
Objective: Neurogenic thoracic outlet syndrome (nTOS) is a rare compression neuropathy, and establishing a firm diagnosis can be challenging. Interscalene nerve blocks with Ropivacaine and Dexamethasone have been proposed in cases with typical symptoms and without evident pathology of the thoracic outlet (i.e., disputed nTOS) to establish the diagnosis. The aim of this study was to evaluate the effectiveness of interscalene nerve block for long-term pain relief in patients with true and disputed nTOS. Methods: Patients between 18 and 90 years of age with either true or disputed nTOS were prospectively included in the study. All patients received an interscalene nerve block with Ropivacaine and Dexamethasone. At baseline, 2, 6, 12, and 24 weeks after infiltration, minimum and maximum pain levels were assessed using the numeric rating scale (NRS 0–10). Furthermore, arm function was assessed using the Quick-DASH, and health-related quality of life was assessed by means of the SF-12 questionnaire. Statistical analysis was performed with SPSS version 29.0 using the Wilcoxon signed rank test and t-test for paired samples. A p-value below 0.05 was considered statistically significant. Results: A total of 21 patients were included in the study. There was a significant decrease in the minimum (Pmin) and maximum (Pmax) mean pain levels at 2 and 6 weeks after the baseline. Thereafter, 12 patients dropped out of the study due to surgery. In the remaining nine patients, pain levels remained significantly lower than baseline at 12 and 24 weeks after infiltration. Quick-DASH scores as well as the physical domain of the SF-12 showed significant improvement compared to baseline. Conclusions: In patients with true and disputed nTOS, long-term pain relief can be achieved with the interscalene nerve block with Ropivacaine and Dexamethasone. Additionally, the study indicated an improvement in arm function and health-related quality of life. In patients with disputed nTOS, the interscalene nerve block may be a useful tool to establish the diagnosis of clinically relevant true nTOS. Key points: Question: Does a scalene nerve block with Ropivacaine and Dexamethasone lead to long-term pain relief in patients with a neurogenic thoracic outlet syndrome (nTOS)? Findings: A scalene nerve block with Ropivacaine and Dexamethasone leads to significant pain relief, as well as an improvement in arm function and health-related quality of life for patients with a neurogenic TOS. Meaning: This study provides new insights into the diagnostic of neurogenic TOS and may be used as a short- and long-term pain therapy.